Swedish opinion 1983 - Boalt, Gunnar; Ekman, Gunnar; Hultgren, Sten; Stiftelsen för Opinionsanalyser (Stiftelsen för opinionsanalyser, 1984)
This dataset contains information from the fifth survey of the collection of Swedish opinion surveys. The 1983 survey was carried out in a somewhat different way than the previous surveys. Three questionnaires were used, each containing approximately 275 questions. 104 questions were put in all three questionnaires, and in all there were 538 different questions. Each questionnaire was answered by approximately 900 persons. The questionnaires were compiled with regard to the debate occurring in media during the last quarter of 1982 and the first of 1983. Many of the questions are replications of questions asked in previous surveys, some of the questions are excluded and a number of questions are added. New questions dealt with: reasons for not wanting more children; own and parents country of origin, citizenship and thoughts of emigration; right to vote for immigrants, and Swedes living abroad; adoption; moral, ability and behaviour within a number of occupational groups; groups favoured/unfavoured in the wage negotiations; issues important for the unity within the bourgeoise parties; opinion on how the government succeeded in carrying out their electoral promises and how they are dealing with other problems; opinion on a number of political goals; reasons why social democrats and the bourgeoise parties can´t cooperate; conception of justice; tobacco, alcohol and drugs.

This dataset contains information from the fifth survey of the collection of Swedish opinion surveys. The 1983 survey was carried out in a somewhat different way than the previous surveys. Three questionnaires were used, each containing approximately 275 questions. 104 questions were put in all three questionnaires, and in all there were 538 different questions. Each questionnaire was answered by approximately 900 persons. The questionnaires were compiled with regard to the debate occurring in media during the last quarter of 1982 and the first of 1983. Many of the questions are replications of questions asked in previous surveys, some of the questions are excluded and a number of questions are added. New questions dealt with: reasons for not wanting more children; own and parents country of origin, citizenship and thoughts of emigration; right to vote for immigrants, and Swedes living abroad; adoption; moral, ability and behaviour within a number of occupational groups; groups favoured/unfavoured in the wage negotiations; issues important for the unity within the bourgeoise parties; opinion on how the government succeeded in carrying out their electoral promises and how they are dealing with other problems; opinion on a number of political goals; reasons why social democrats and the bourgeoise parties can´t cooperate; conception of justice; tobacco, alcohol and drugs.
Svensk opinion 1983
SVOP83
Keywords: INTERNAL POLITICS; INRIKESPOLITIK; Media; Media; Working conditions; Arbetsförhållanden; Political behaviour and attitudes; Politiska beteenden och attityder; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap